Prediction of the flow inside a micro gas turbine combustor - Eldrainy, Yehia A.; Muhamad Ridzwan, Johann Jeffrie; Mohd. Jaafar, Mohammad Nazri (Faculty of Mechanical Engineering, 2008)
The main purpose of this study is to predict the flow dynamics inside a micro gas turbine combustor model. The flow field inside the combustor is controlled by the liner shape and size, wall side holes shape, size and arrangement (primary, secondary and dilution holes), and primary air swirler configuration. Air swirler adds sufficient swirling to the inlet flow to generate central recirculation region (CRZ) which is necessary for flame stability and fuel air mixing enhancement. Therefore designing an appropriate air swirler is a challenge to produce stable, efficient and low emission combustion with low pressure losses. Four axial flat vane swirlers with 20 °, 30 °, 45 ° and 60 ° vane angle corresponding to swirl number of 0.27, 0.42, 0.74, and 1.285 respectively were used in this analysis to show vane angle effect on the internal flow field. The flow behavior was investigated numerically using CFD solver FLUENT 6.2. This study has provided physical insight into the flow pattern inside the combustion chamber. Results show that the swirling action is augmented with the increase in the vane angle, which leads to increase in the turbulence strength, recirculation zone size, and amount of recirculated mass. However, all these happen at the expense of the increase in pressure losses. In case of 20 ° swirler (swirl number < 0.4), the produced swirling flow is not enough to generate CRZ.